SELECTION OF EFFECTIVE DEMULSIFYING AGENTS FOR OIL-WATER EMULSIONS BREAKDOWN - BAYAMIROVA, Ryskol; TOGASHEVA, Aliya; ZHOLBASSAROVA, Akshyryn; BISSENGALIEV, Max; KUNAYEVA, Gaukhar; KULIYEV, Murad; BORIBEK, Shynggys (Studia Universitatis Babeș-Bolyai Chemia, 2020)
Crude oil processing often requires the extraction of large amounts of water. Crude oil often mixes with water to form water-in-crude oil emulsions as a result of exposure such as high shear at the wellhead and natural surfactants in crude oil. These emulsions are undesirable and require demulsification to remove dispersed water and associated inorganic salts in order to meet production and shipping specifications. In addition, demulsifying these crude oil emulsions reduces corrosion and catalyst and consistently maximizes the overall profitability of crude oil production. The article looks into the results of tests on the selection of a demulsifier for the breakdown of water-in-oil emulsion mixtures at different settling times and temperatures depending on the specific consumption of the chemical agent, the effect of various demulsifiers on emulsions breakdown. The process of oil desalination with and without the addition of demulsifiers is considered. Desalination is carried out stepwise. Research results have shown that proxanol 305/50 is the most effective demulsifier.